2004
DOI: 10.1373/clinchem.2003.027391
|View full text |Cite
|
Sign up to set email alerts
|

Serum S100B in Pregnancy-Related Hypertensive Disorders: A Case–Control Study

Abstract: precision has been stated to be 11.6 mol/L (10 ). The imprecision (CV) for total bilirubin measurements on the Olympus analyzer ranged from 4.2% at a concentration of 123.1 mol/L to 2.8% at a concentration of 372.8 mol/L.The ability to measure bilirubin concentrations in newborns simply, rapidly, accurately, cost-effectively, and with minimal risk or discomfort has taken on increased importance in the current environment of managed care, capitation, litigation, and brief postpartum hospitalization. Measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 25 publications
2
14
0
1
Order By: Relevance
“…In any case, one should assume that large increases in S100B concentrations in fetal and/or placental tissues would lead to an appreciable increase in the maternal blood in spite of the dilution effect attributable to the higher volume of the maternal bloodstream. Obviously, S100B can also derive from maternal tissues, as reported recently (36 ). Because all pregnant women enrolled in the present study were in healthy condition and had no detectable overt neurologic syndromes, the possibility that the protein originates from damaged maternal nervous system cells seems fairly remote.…”
Section: Discussionsupporting
confidence: 62%
“…In any case, one should assume that large increases in S100B concentrations in fetal and/or placental tissues would lead to an appreciable increase in the maternal blood in spite of the dilution effect attributable to the higher volume of the maternal bloodstream. Obviously, S100B can also derive from maternal tissues, as reported recently (36 ). Because all pregnant women enrolled in the present study were in healthy condition and had no detectable overt neurologic syndromes, the possibility that the protein originates from damaged maternal nervous system cells seems fairly remote.…”
Section: Discussionsupporting
confidence: 62%
“…In hypoxic microenvironments, DAMPs may not be oxidized and denatured and thus, may promote inflammation [50] through ligation of receptors, such as RAGE, TLR2, and TLR4, which are expressed in immune system cells [51]. S100 and HMGB1 are proteins that behave as DAMPs [51,52]. High cytoplasmic expression of HMGB1 occurs in decidual cells of preeclamptic patients [53], and S100B is increased in amniotic fluid during preeclamptic pregnancies [54] in direct relation to oxidative stress [55].…”
Section: Tlrs In Preeclampsiamentioning
confidence: 99%
“…S100B is one of the members of the S100 protein family containing 21 types of EF‐hand Ca 2+ binding proteins. Aberrant S100B expression has been reported in different pathologies, including neurodegenerative disorders and cancers . It is reported that circulating S100B concentrations are the biomarker of malignant melanoma .…”
Section: Introductionmentioning
confidence: 99%